Charlotte Bronte's Jane Eyre - Milton, Joyce (Barron's book notes, 1984)
A guide to reading "Jane Eyre" with a critical and appreciative mind. Includes background on the author's life and times, sample tests, term paper suggestions, and a reading list.1